Senandung Cinta Penuh Makna: Analisa Filosofis Puisi Jalaluddin Rumi - Miswari, Miswari (Al Mabhats : Jurnal Penelitian Sosial Agama, 2018)
This paper aims to analyze philosophically on Jalaluddin Rumi's poems that have been compiled and transcribed by the researcher of his thinking, Reynold A. Nicholson. Jalaluddin Rumi conveys his teachings with symbolic expressions in poetic form that are difficult to understand. The author tries to make a systematic narrative by using relevant references in order to interpret the meaning of the teachings of Jalaluddin Rumi. Penulis menemukan ajaran Jalaluddin Rumi adalah ajaran tentang pengalaman sufi yang menganut ajaran tasawuf falsafi (gnosis). This teaching emphasizes the esoteric aspect. A sad and longing bitter experience, in mystical experience is true beauty. This experience offers true beauty and eternal happiness. So keep away from being hateful towards people who are different from her. In hateful times, falsely accusing each other, claiming their own true beliefs, so that humans become very easy to hate each other and hostile, the gnosis taught by Jalaluddin Rumi becomes indispensable to mankind today as the foundation for building unity and harmonization in life.